The Effectiveness of Using the English Subtitle of Western Friendly Child Movie Media to Enhance Students’ English Vocabulary - Pratiwi, Rita Yulia; Arafiq; Amrullah (Journal of English Education Forum (JEEF), 2025)
The purpose of the study is to investigate the impact of using English subtitles from Western child-friendly movies on students' English vocabulary. This research was experimental research and implemented a pre-test post-test group design. The sample of thsi research was the students from 9th grade students of SMP 1 Praya which consisted of 50 students. This research used observation and test as the research instruments. The result of this research showed that the independent sample t-test revealed a significance (2-tailed) value of 0.000. Since this value is less than the standard threshold of 0.05, it indicates that the difference between the mean scores of the control and experimental classes is statistically significant. This finding confirms that the observed variation in scores is unlikely to have occurred by random chance. Therefore, it can be concluded that the intervention applied to the experimental class using English subtitles in Western child-friendly movies had a substantial and measurable impact on improving students’ vocabulary proficiency compared to the traditional teaching methods employed in the control class. These findings highlight the effectiveness of using English subtitles in Western child-friendly movies as a teaching tool for improving vocabulary. The experimental class's significant improvement compared to the control class's limited progress underscores the potential of innovative methods over traditional teaching approaches in enhancing students’ English vocabulary proficiency.